65 Effect of exogenous fibrolytic enzymes on untreated or ammonia fiber expansion (AFEX) - treated wheat straw on in vitro semi-continuous culture fermentation using the rumen simulation technique (RUSITEC). (7th December 2018) - Saleem, A; Ribeiro, G; Alipour, D; Brand, T; Santos, L; Yang, W; McAllister, T
Abstract: This study investigated the effect of AFEX treated wheat straw and exogenous fibrolytic enzymes (Viscozyme ® ) on feed digestibility, rumen fermentation, and microbial protein synthesis using the rumen simulation technique (RUSITEC). The experiment was a completely randomized block design with four treatments assigned to sixteen vessels (4/treatment) in two RUSITEC apparatus in a 2 × 2 factorial. Treatments were: 30% concentrate + 70% wheat straw; and 30% concentrate + 70% AFEX treated wheat straw with or without enzyme. The study consisted of 8-d adaptation and 7-d for sample collection. Data were analyzed by the PROC MIXED procedure of SAS with fixed effects of AFEX, enzyme and their interaction. No interaction between AFEX-sraw and enzyme occurred. AFEX-straw versus untreated straw had greater ( P < 0.01) digestibility of DM (69.6 vs. 38.3%) NDF (61.6 vs. 36.8%), ADF (61.4 vs. 36.0%) and CP (68.3 vs. 24.0%). Dry matter, OM and NDF digestibility of AFEX-straw was greater ( P < 0.05) with enzyme addition, with no effect of enzyme on untreated straw. Total microbial N production was greater ( P < 0.01) for AFEX-straw (72.9 mg/day) than for untreated straw (63.1 mg/day). Production of total gas and CH4 was greater ( P < 0.01) with AFEX-straw than untreated straw. AFEX-straw increased ( P < 0.01) NH3 -N and total VFA production and proportion of propionate but decreased ( P < 0.01) that of acetate. As a result, the ratio of acetate to propionate was reduced ( P < 0.01) with AFEX versus untreated straw. Enzyme addition did not affect VFA production or VFA profiles. The number of protozoa was lower ( P < 0.01) with AFEX straw than untreated straw. The results indicate that AFEX increased ruminal digestibility of wheat straw and microbial protein synthesis and improved rumen fermentation, with more propionate production a response that was heightened by enzymes.